Country report Malaysia: role of university education in rural development - Mohd. Yassin, Sulaiman; Zainuddin, Alang Perang
Malaysa has five universities that have been charged with the training of manpower to meet national needs. The various academic programmes in the five universities have been coordinated to avoid unnecessary duplication and ineffective use of resources as well as to ensure excellence in the frogrammes. Focussing on the development of the human potential, various university programmes are geared towards this aim. Leadership is provided in research, consultancy and other forms of public service in various fields in which the universities have expertise in. Student extra-curricular and community-service programmes, both the ad-hoc and formal types are also administered with the central purpose of providing them with adequate experiences to develop sensitivity. appreciation of and their leadership potential in the development of the rural communities that they inadvertantly will serve in their various capacities. At least one Malaysian university has made a formal commitment to have its own formal Extension and Continuing Education programme that again supports the role of the university in rural development while allowing it to be in touch with the rural development scene in its endeavour to remain relevant.